The Effect of Institutional Ownership and Leverage towards Profit Management in Consumer Goods Industry Listed in BEI - Bambang Leo Handoko (Bina Nusantara University, 2015)
Earning management is usually used by the company as shortcut to make up their financial statement to fulfill some criteria for certain purpose. This research is empirical research which aimed is to examine the influence of institutional ownership and leverage to earnings management. This study takes sample from companies in the consumer goods sector at the Jakarta Stock Exchange, which were published in financial report from 2008-2011. The method of analysis of this research used multiple regression analysis. The results of this study show that (1) institutional ownership had not significant influence to earnings management sig.0,129>0,05, (2) leverage had not significant influence to earnings management sig. 0,481>0,05 and (3) simultaneously of institutional ownership and leverage had not significant influence to earnings management0,249>0,05.